The Anti-Influenza Virus Drug Rimantadine Has Trypanocidal Activity - Kelly, John M. (American Society for Microbiology, 1999)
We report here that bloodstream forms of the African trypanosome, Trypanosoma brucei, are sensitive to the anti-influenza virus drug rimantadine (50% inhibitory concentration of 1.26 μg ml(−1) at pH 7.4). The activity is pH dependent and is consistent with a mechanism involving inhibition of the ability to regulate internal pH. Rimantadine is also toxic to the trypanosomatid parasites Trypanosoma cruzi and Leishmania major.